Genetic Variability and Association of Forage Quality Characters in Strains of Lasiurus Sindicus Henr - Gupta, Ashok Kumar; Yadav, M S; Krishna, G V.S.R (Annals of Arid Zone, 2016)
Coefficients of variation, heritability, genetic advance, correlations and path analysis were studied in relation to eight forage quality characters of 33 strains of Lasiurus sindicus. Wide range of variations were observed in the strains for silica, dry matter, lignin and crude protein which exhibited high heritability and genetic advance. Neutral detergent fibre (NDF), acid detergent fibre (ADF), lignin and cellulose had positive and significant inter-correlations at both, genotypic and phenotypic levels. Path analysis revealed high direct effect of ADF and cellulose on dry matter per cent. Considering both, direct and indirect effects, cellulose. ADF and protein assume importance in the selection of high forage yielding and nutritive strains of L. sindicus.